Effect of Prenatal Perineal Massage on Postpartum Perineal Injury and Postpartum Complications: A Meta-Analysis. (14th July 2022) - Chen, Qiuxia; Qiu, Xiaocui; Fu, Aizhen; Han, Yanmei
Abstract : Background . The efficacy of perineal massage is controversial. The study was aimed at comparing the effects of perineal massage on perineal injury and complications. Methods . PubMed, Embase, the Cochrane Library, and ISI Web of Science were searched for literature on the relationship between prenatal perineal massage and postpartum perineal injury and complications until April 2022. Indicators included postpartum perineal tears, perineotomy, postpartum perineal pain, natural labour, and postpartum incontinence. Finally, RevMan5.4 software was used to analyze the extracted data. Results . A total of 6487 subjects in 16 studies were included, with 3211 who received perineal massage and 3276 did not. There was no significant difference in 1-2 degree perineal tearing between the intervention group and the control group (RR = 0.96, 95% CI [0.90, 1.03], P = 0.30 ), and there was no heterogeneity between studies (P = 0.62, I 2 = 0 % ), indicating publication bias. Compared with the control group, prenatal perineal massage significantly reduced the incidence of 3-4 degree perineal tears (RR = 0.56, 95% CI [0.47, 0.67], P < 0.00001 ), and there was no heterogeneity between studies (P = 0.16, I 2 = 30 % ), indicating publication bias. Compared with the control group, prenatal perineal massage reduced the risk of lateral perineal resection (RR = 0.87, 95% CI [0.80, 0.95], P = 0.001 ), and there was no heterogeneity between studies (P = 0.14, I 2 = 31 % ), and there was no publication bias. Compared with the control group, prenatal perineal massage reduced the risk of postpartum pain at 3 months (RR = 0.64, 95% CI [0.51, 0.81], P = 0.0002 ). There was no significant heterogeneity among studies (P = 0.23, I 2 = 31 % ). Conclusion . Compared with no prenatal perineal massage, prenatal perineal massage can reduce the risk of perineal injury, the incidence of lateral perineal resection, and the incidence of long-term pain.